Faculty perceptions of technology literacy in the community college curriculum - Samet, Oneka (Kansas State University, 2021)
A 2002 report by the National Academy of Engineering and National Research Council proposed a model of technological literacy knowledge necessary for all citizens that could be integrated into the academic curriculum. The report recommended that career and technical education (CTE) and general education (GE) faculty include technology literacy competencies into the academic curriculum. The report also indicated that educators would have difficulty making the case that the study of technology must be included in the curriculum. The initial task for educators begins with building a unified understanding of which technology literacy skills are most needed and using this as a starting point for incorporating skills into the college curriculum. Community colleges are open access and mainly serve low-income and disadvantaged populations looking for low-cost options in career preparation or acquiring an advanced degree. In 2012, the American Association of Community Colleges put out a call-to-action for community college leaders to redefine the mission of the community college ensuring that students are learning current technology skills to advance personally and professionally. This investigation addresses GE and CTE faculty perceptions and attitudes toward integrating technology literacy competencies into the community college curriculum. This research replicated the methods followed in a study conducted by Kalfsbeek in 2007 and builds evidence to validate the original study’s findings. This replicated study highlights key differences between GE faculty and CTE faculty in the community college. This multilevel concurrent research used an online, anonymous survey with 24 Likert-type quantitative questions and several open-ended questions. The population of the study was 157 full-time faculty at a community college in Michigan. Results revealed differences in the perceptions of GE faculty and CTE faculty across different disciplines, highlighting the need for more formal guidelines for inclusion of technology literacy competencies across the curriculum. The groundwork for the findings of this research is underpinned by Bloom’s taxonomy and used to create course learning outcomes that can be easily integrated into creating a shared curriculum.
Keywords: Technology literacy; Community college; Digital divide; General education; Career and technical education; Digital literacy